Applying Gestalt Laws through Somatic Sensibility - Claudia Núñez-Pacheco (Diseña, 2022)
Attending to the need to integrate somatic sensibilities into design education, this paper provides a walkthrough of a workshop activity devoted to introducing Gestalt laws through the cultivation of somatic sensibility. Instead of following a solely visually-oriented path to learning Gestalt laws, students were asked to use their senses and materials as vehicles to represent their felt, inner experience through their designs. By applying the proposed steps, it was observed that certain patterns of responses reporting on movement, intensity, and dissipation of awareness were associated with specific Gestalt laws. This article reports on the first approximations of this approach, suggesting future paths for design educators, such as the integration of both constraints and whole-body interactions with materials as students increase their somatic sensibility.